1 A double-blind randomised control trial of high-volume image guided injections in achilles and patellar tendinopathy in a young active population. Issue 5 (26th September 2022) - Barker-Davies, Robert M; Baker, Polly; Watson, James; Goodall, Duncan; Wheeler, Patrick C; Nicol, Alastair M; Fong, Daniel TP; Lewis, Mark P; Bennett, Alexander N
Abstract : Background: Chronic tendinopathy is a significant burden in physically active populations. High-volume image-guided injection (HVIGI) proposes to strip away associated neovascularity, disrupt painful nerve ingrowth and facilitate rehabilitation. Methods: The objective was to investigate the efficacy of HVIGI with and without steroid relative to placebo. The study design was a three-arm block randomised control trial in a tertiary rehabilitation centre. Sixty-two participants were recruited between 25 May 2016 and 5 March 2020. Participants were men aged 18–55 with, Achilles or patellar tendinopathy of at least 6-months chronicity who had not improved with conservative management including shockwave, Ultrasound (US) evidence of neovascularisation, tendon thickening and echogenic changes. Participants were randomly assigned to control (3ml subcutaneous 0.5% Bupivacaine) or HVIGI (10 ml 0.5% Bupivacaine and 30 ml normal saline US guided between tendon and underlying fatpad) or HVIGI with steroid (0.25 ml 100 mg/ml hydrocortisone). Clinicians and assessors were blinded. All participants were supervised through a pain-guided progressive loading programme for 6-months post injection. The primary outcome measures were the Victoria institute of sport assessments for Achilles and patellar tendinopathy (VISA-A and VISA-P) and visual analogue scale (VAS)-pain at 6-months. Results: VISA improved by 22.8 ((95% CI) 10.4 to 35.3, effect size (ES) 1.51) in control (n=21), 18.6 (9.1 to 28.0, ES 1.31) in HVIGI (n=21) and 18.5 (3.4 to 33.6, ES 0.88) in HVIGI with steroid (n=20) groups. VAS-pain improved by 15 ((IQR) -38.75 to 8, ES 0.39) in control, 13 in HVIGI (-34.0 to 3.75, ES 0.47) and 27 (-38.0 to-1.0, ES 0.54) in HVIGI with steroid groups. Main effects for time were significant (p<0.001) but not group (p≥0.48) with no group-time interaction (p=0.71). One participant was lost to follow-up from each group for whom multiple imputation was used. No adverse events occurred. Conclusions: Data does not demonstrate superiority of HVIGI over control injection. Pain-guided progressive loading remains the mainstay of treatment.